(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In our country, in recent years, strengthening social protection of citizens and reducing poverty have been identified as a priority area of state policy in terms of reforming the national economy, and providing the population with new jobs and a guaranteed source of income, qualified medical and educational services, and decent living conditions have reached a qualitatively new level. As a result of the reforms carried out over the past five years, the necessary political, legal, socio-economic, and scientific and educational foundations for building a New Uzbekistan have been created in our country.